Investigation of the changes in microstructure and transport properties of leached cement pastes accounting for mix composition. (January 2016) - Phung, Quoc Tri; Maes, Norbert; Jacques, Diederik; De Schutter, Geert; Ye, Guang
Abstract: Ca-leaching of cement-based materials induces detrimental effects on properties related to long-term durability. A better understanding of leaching degradation in terms of alterations in mineralogy, microstructure, and transport properties is important for long-term assessments of concrete and reinforced concrete structures used in nuclear waste disposal systems or in hydro structures. However, the decalcification process is not easy to study because it is extremely slow. In this study, an ammonium nitrate (NH4 NO3 ) solution of 6 mol/l was used to accelerate the leaching kinetics. The experiments were performed on cement paste samples with different water/powder (w/p) and limestone filler (LS) replacement ratios. Both the change of sample mass over time and the amount of calcium ion leached out were monitored during the test. Different post-analysis techniques including SEM/SEM-EDX, XRD/QXRD, MIP, ion chromatography, and N2 -adsorption were used to characterize the microstructural and mineralogical changes. The effect of accelerated leaching on transport properties was studied by measuring the changes in water permeability and diffusivity of dissolved gases. Results showed that the square-root-time law of degradation was applicable under accelerated conditions. Both higher w/p ratios and LS replacements increased the rate of leaching propagation; the former had a more significant effect. The accelerated leaching significantly altered the microstructure of the cement paste to a material with a higher specific surface area, increased total porosity and a shift to larger pore sizes. Those changes led to a significant increase in water permeability (one to two orders of magnitude) and diffusivity (less than one order) depending on degradation state.